2018
DOI: 10.1016/j.jfma.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Association between Helicobacter pylori infection and cognitive impairment in the elderly

Abstract: Our findings disclosed a positive association between serum H. pylori level and cognitive impairment, which provides important information for the primary prevention of cognitive impairment through the eradication of H. pylori.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Previous researches have been performed to examine the association between H. pylori infection and various cognitive outcomes, including all-cause and AD dementia. However, the association is not fully understood [ 23 26 ]. Our results are limited to observational studies suggest that H. pylori infection may be an independent risk factor for all-cause dementia, but not for AD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches have been performed to examine the association between H. pylori infection and various cognitive outcomes, including all-cause and AD dementia. However, the association is not fully understood [ 23 26 ]. Our results are limited to observational studies suggest that H. pylori infection may be an independent risk factor for all-cause dementia, but not for AD.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have established association between H. pylori infection and cardiovascular diseases [59, 60], yet a few other studies failed to find any association [61, 62]. Chronic inflammation secondary to ongoing H. pylori infection may play a role in developing or worsening Alzheimer dementia [6365] and vascular dementia [66]. The association between compromised bone mineral density and H. pylori infection has been supported by recent investigations [52, 67].…”
Section: Stomachmentioning
confidence: 99%
“…[ 1 ] HP seropositivity in patients has been found to be associated with the increased incidence of various of diseases, including cardiovascular, respiratory, extragastroduodenal, digestive, nervous, and other autoimmune diseases. For example, recent studies have shown that HP may be closely related to cognitive impairment, [ 10 ] neurodegenerative diseases, [ 11 ] including Parkinson disease, [ 12 , 13 ] Alzheimer disease, [ 14 ] depression, [ 15 ] the digestive system cancers such as CRC. [ 16 20 ] CRC or colorectal adenomas is closely correlated with higher incidence of HP infection in patients.…”
Section: Introductionmentioning
confidence: 99%